Media Pembelajaran Inovatif - Efifani Krismitha Saroro; Indah Setyo Wardhani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Amid the demands of the 21st-century industrial revolution and digital skills, integrating innovative learning media is vital in education. This study highlights its role in promoting interactive learning and enhancing student engagement. A literature review of books, articles, and journals shows that digital technology and multimedia tools boost motivation, understanding, and collaboration. The article emphasizes selecting the right media to create an engaging and effective learning environment.